2020
DOI: 10.1007/s40789-020-00311-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the formation of graphene nanocapsules from coal tar pitch

Abstract: It has recently been reported that coal tar pitch (CTP) can be utilised as raw material for the production of graphene nanocapsules (GNCs) because it is formed by a great quantity of aromatic organic compounds (which promote the rearrangement of double bonds by a process of polymerisation). Due to the importance of graphene and the search for a non-expensive methodology to produce it, this work used CTP to synthesise GNCs using an in situ activation technique at low temperatures and evaluating the effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…(Figure ). ,,,, Similar to the conventional source-derived graphene, the LCP-based graphene derivatives also show similar charge storing ability and efficiency as reported by different studies. ,,,,, As mentioned earlier, the coal-based graphene derivatives are found to be efficient electrode materials for energy storage applications, as supported by several research studies. Zhou et al reported the use of graphitized anthracite-based graphene derivatives for their electrochemical analysis with 6 M KOH (aqueous electrolyte) in a three-electrode supercapacitor cell at room temperature.…”
Section: Energy Applications Of the Synthesized Graphene Derivativessupporting
confidence: 65%
See 2 more Smart Citations
“…(Figure ). ,,,, Similar to the conventional source-derived graphene, the LCP-based graphene derivatives also show similar charge storing ability and efficiency as reported by different studies. ,,,,, As mentioned earlier, the coal-based graphene derivatives are found to be efficient electrode materials for energy storage applications, as supported by several research studies. Zhou et al reported the use of graphitized anthracite-based graphene derivatives for their electrochemical analysis with 6 M KOH (aqueous electrolyte) in a three-electrode supercapacitor cell at room temperature.…”
Section: Energy Applications Of the Synthesized Graphene Derivativessupporting
confidence: 65%
“…(Figure 19). 46,84,96,100,125 Similar to the conventional sourcederived graphene, the LCP-based graphene derivatives also show similar charge storing ability and efficiency as reported by different studies. 57,72,80,84,98,126−128 As mentioned earlier, the coal-based graphene derivatives are found to be efficient electrode materials for energy storage applications, as supported by several research studies.…”
Section: Energy Storage Applicationssupporting
confidence: 60%
See 1 more Smart Citation
“…13−15 Among these, the naturally available coal is seen as a promising candidate for graphene synthesis with optimal quality and yield, as reported in the literature. 18,21 Several studies have described the use of coal as a potential carbonaceous source for high-valued graphene production. 22−25 However, most of the techniques involved require high energy, high temperature, and drastic treatments with high maintenance, resulting in the high cost of the synthesized graphene derivatives, and the highgrade coals were utilized as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of graphene applications and its continuous introduction into newer fields, there has been a huge demand for this unique functional carbon material in large scale. , Therefore, researchers are now exploring other natural carbonaceous materials for their suitability as a precursor for low cost, environment friendliness, and large-scale production of graphene and its derivatives. Among these, the naturally available coal is seen as a promising candidate for graphene synthesis with optimal quality and yield, as reported in the literature. , Several studies have described the use of coal as a potential carbonaceous source for high-valued graphene production. However, most of the techniques involved require high energy, high temperature, and drastic treatments with high maintenance, resulting in the high cost of the synthesized graphene derivatives, and the high-grade coals were utilized as precursors. ,, This drawback in the synthesis strategy of coal-derived graphene has motivated the researchers for the investigation of a simpler yet more effective synthetic pathway for graphene derivatives, using low-grade coal feedstock as the starting material.…”
Section: Introductionmentioning
confidence: 99%